2023
DOI: 10.23917/bik.v16i2.1882
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Indonesian Nurses Toward Non-Reported Needle Stick Injury in Saudi Arabia: A Phenomenological Study

Akhir Fahruddin,
Yayi Suryo Prabandari,
Martinus Sutena
et al.

Abstract: Non-reported needle stick injury (NSI) is still a major problem faced by nurses when working in health services in Saudi Arabia viewed from the perspective of occupational health and safety (OHS). Knowing the behavior of nurses in the workplace can have implications for the OHS culture. Objective: To explore the behavior of Indonesian nurses towards non-reported NSI in health services in Saudi Arabia. This study used a qualitative method with a phenomenological approach. The research subjects used typical case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
0
2
1
Order By: Relevance
“…The results of qualitative research conducted on 12 informants showed that 10 nurses stated they were happy, enthusiastic, and enjoyed their work experience in Saudi Arabia. This explains that this research is not in line with previous research that shows that Indonesian nurses who work in health services in Saudi Arabia face burnout challenges (Fahruddin et al, 2023). Nurses feel more appreciated when working in Saudi Arabia, so nurses can be more enthusiastic about their work, even though they have to face various challenges at work, such as the behavior of patients who have a strong character or the number of patients that exceeds the capacity of the number of nurses.…”
Section: Burnoutcontrasting
confidence: 67%
See 2 more Smart Citations
“…The results of qualitative research conducted on 12 informants showed that 10 nurses stated they were happy, enthusiastic, and enjoyed their work experience in Saudi Arabia. This explains that this research is not in line with previous research that shows that Indonesian nurses who work in health services in Saudi Arabia face burnout challenges (Fahruddin et al, 2023). Nurses feel more appreciated when working in Saudi Arabia, so nurses can be more enthusiastic about their work, even though they have to face various challenges at work, such as the behavior of patients who have a strong character or the number of patients that exceeds the capacity of the number of nurses.…”
Section: Burnoutcontrasting
confidence: 67%
“…During the pandemic, more than 15 nurses chose not to continue their contracts and returned to Indonesia. This is caused by changes in working hours during the pandemic, increased workload, and fatigue at work (Fahruddin et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation